Akulturasi Budaya Tradisi Ruwatan Anak Tunggal Dalam Ajaran Islam di Desa Mandirejo Kecamatan Merakurak Kabupaten Tuban - Jamal Ghofir; Daffa Yulia Pratama (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2023)
Ruwatan is a purification ceremony carried out to prevent a child from having bad luck by holding a puppet show. Ruwatan an only child is a hereditary tradition from ancestors which is still preserved by the people, especially the Javanese who believe in it. The ruwatan tradition is considered as something sacred by some Javanese people. Ruwatan is carried out by holding a wayang play performance of Murwakala accompanied by chanting of mantras, gamelan and gending which are believed to ward off evil. The ruwatan ritual of an only child in modern times is carried out by combining the teachings of previous ancestors with islamic teachings.